Technological Advances and Educational Transformation: Towards Inclusive Education - Villatoro Moral, Sofía (2025)
The incorporation of technology in educational settings, emphasizing its progression from basic tools to advanced resources like virtual classrooms and augmented reality, has significantly redefined teaching and learning modalities. This examination evaluates technology’s influence on educational ethics and values, highlighting its function in fostering inclusivity and enhancing accessibility. The manuscript probes the nuanced distinction between technological integration and adaptation within pedagogical frameworks, emphasizing a profound alteration in educational methodologies beyond mere supplementation. Furthermore, the impact of the COVID-19 pandemic in accelerating the transition towards digital educational models and e-learning is scrutinized. Challenges and prospects associated with technological adoption are discussed, encompassing the imperative for teacher training in nascent technologies. Additionally, the manuscript contemplates the future trajectory of education with the prospective implementation of artificial intelligence, weighing its potential benefits against ethical and practical challenges.